If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 10n = -60 Solving 10n = -60 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Divide each side by '10'. n = -6 Simplifying n = -6

| 5y+15=80 | | k-8=-15 | | 14x+4=116 | | -74=6+10x | | 2x-x-10=-13 | | 5=x-(-28) | | 2(6-4d)=2s-9d | | -4x+8+12=44-48 | | -17-v=-5 | | 8x-6=130 | | 3(a-8)+7=5(a+2)-3a-19 | | (9y^2-6y+9)-(5y^2-6y+8)= | | -12-n=-10 | | 2(a-5)=2(q+5) | | 2x+2=89 | | -9x-1.4=5.8 | | -11+x=-11 | | 15x-5=50 | | X^2+36+180=0 | | -89=-80-x | | 2y-15+3y=60 | | 8+15p-1=8p+98-6p | | -54=m+(91) | | 117=n+40 | | 14x+3=7x+9 | | 15x+3.5=2 | | 3.1+7.3= | | 69=x-(-5) | | 69+25= | | 7+21m=42+14m | | 3(5x-4)=8x+12 | | A*4-60=A | | 3(d-8)-5=9(d+2)-1 | | x^2+10x+25-y^2=0 | | 6k-2s=7-2k | | x(3+x)+20=X^2-(x-5) | | -5z-13z+10=10+7z+3 | | 5(4z-1)-4(z+2)=14(z+1) | | 18x= | | -12-12-4x=32-28 | | 2(7+x)=11 | | 9y+7=8y-5 | | 6-2x=5x-9x+9 | | 5(x-6)+8=7(x+2)-2 | | -8(t+1)=0 | | .80(x-100)=450 | | 4(3c-1)-5=10c+9 | | -6m+7-6m+12=3m-5m+5-8m+2 | | (5a+3)+(7a+5)= | | 4x=49+3 | | 5(4x-3)=21x | | x-50=.80(x-100) | | y=0.2189x+15.61 | | -16t^2+80t-96=0 | | w^2+13w-30= | | (6x+3y+1)-(5x+2y-3)= | | w^2-w-30= | | 6(y-2)=4y-22 | | w^2+19w+18= | | 8(4c-1)-18=30c+8 | | .592n+60=5n-12-n | | 4(1+c)=3(c-4) | | 3x-2(7)=x | | 6-8x=7x-10x-29 | | p^2-21p+20= |